Perancangan Interior Hatten Wines Gallery di Bali - Fenny K. D, Lydia Angeline Soesanto Hedy C. Indrani (Intra, 2013)
Wine is a beverage made from fermented fruit, especially grapes, which have been widely recognized by society since time immemorial. For Indonesian people, wine has been popular, and consumption levels increased over time. But the majority of Indonesian people are not familiar with Indonesian local wine, and they havenât yet understand about how to enjoy the wine. Therefore, it takes a facility as a means of education, information, appreciation, and recreational support to provide more insight for the people. Besides design purposes gallery of local wine Indonesia is also to attract foreign tourists to know the uniqueness of Indonesian wine. Efforts are underway to design objects Indonesia local wine gallery is to provide special facilities, which includes lobby, classrooms, winemaking area, area galleries, wine history area, bar, andÂ spa area.